Managing Ethical Challenges in Nursing Practice and Policy - alotaiby , Bedor Algohfaili; Alshareef , Tomooh barakat; alhazmi, Rahaf Hayat; Albshri , Mashael Saad; ageeli, Amnah Ibrahim; almzmomi, Buthaina fraug; Asiri, Sharefah mousleh Ali; Alqarni, Eman Fehaid Saeed; ALMUTAIRI, YASEMEEN JUMYYA; Mahmoodi , Aisha Hamad; Thaker , Asmaa suliman Hadi; Aqeeli, Fatema Ibrahim; et al. (Journal of Ecohumanism, 2024)
Background: Ethical decision is an integrated part of nursing practice since nurses determine the best approach to creating solutions to a certain problem or to resolve a given situation that lacks a moral or professional resolution. This paper aims at presenting ethical dilemmas which occur in various areas of practice, including patients, health care facilities as well as policies. Aim :The purpose of this study is to identify ways in which nurses address ethical concerns in practice and policy, as well as the approaches that are employed to maintain ethical practice and provide client centered care. Methods: This was a descriptive study using both research and gray literature on the current state of ethical dilemmas with focus on interview with nursing professionals to assess the manner in which different ethical dilemmas are managed in health clinical and health policy. Results:Research shows that these challenges pertain to patient self-management, resources management and decision-making on ethical issues. Patient advocacy, for example, and leadership in ethics committees are very crucial in handling of these problems. Conclusion :Since ethical issues play an important role in shaping up a nursing profession and adding quality to the care being provided it is vital to be able to manage these issues. This paper concluded that continuing education and focused leadership were the solution to ethical issues and the creation of ethical culture and practice.